Cuban émigrés and independence in the nineteenth century Gulf world - Muller, Dalia Antonia (Envisioning Cuba., 2017)
During the violent years of war marking Cuba's final push for independence from Spain, over 3,000 Cuban emigres, men and women, rich and poor, fled to Mexico. But more than a safe haven, Mexico was a key site, Dalia Antonia Muller argues, from which the expatriates helped launch a mobile and politically active Cuban diaspora around the Gulf of Mexico. Offering a new transnational vantage on Cuba's struggle for nationhood, Muller traces the stories of three hundred of these Cuban emigres and explores the impact of their lives of exile, service to the revolution and independence, and circum-Caribbean solidarities. While not large in number, the emigres excelled at community building, and their effectiveness in disseminating their political views across borders intensified their influence and inspired strong nationalistic sentiments across Latin America. Revealing that emigres'efforts were key to a Cuban Revolutionary Party program for courting Mexican popular and diplomatic support, Muller shows how the relationship also benefited Mexican causes. Cuban revolutionary aspirations resonated with Mexican students, journalists, and others alarmed by the violation of constitutional rights and the increasing conservatism of the Porfirio Diaz regime. Finally, Muller follows emigres'return to Cuba after the Spanish-American War, their lives in the new republic ineluctably shaped by their sojourn in Mexico.